2017
DOI: 10.1007/s00134-016-4666-z
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring dynamic arterial elastance as a means of decreasing the duration of norepinephrine treatment in vasoplegic syndrome following cardiac surgery: a prospective, randomized trial

Abstract: A haemodynamic algorithm based on dynamic arterial elastance was associated with a shorter duration of norepinephrine treatment and a shorter LOS in the ICU. Use of the algorithm did not alter perfusion parameters or increase the volume of fluid infused. ClinicalTrials.gov Identifier: NCT02479529.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…14e16 In studies assessing the effect of vasopressors, Ea dyn was demonstrated to change while CO did not change. 3,4,14 Ea dyn was demonstrated to be associated to cardiac factors (HR and peak of velocity of aortic blood flow) and vascular factors (arterial compliance and vascular resistance). 3,16 Moreover, no study has demonstrated an association between CO and Ea dyn .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14e16 In studies assessing the effect of vasopressors, Ea dyn was demonstrated to change while CO did not change. 3,4,14 Ea dyn was demonstrated to be associated to cardiac factors (HR and peak of velocity of aortic blood flow) and vascular factors (arterial compliance and vascular resistance). 3,16 Moreover, no study has demonstrated an association between CO and Ea dyn .…”
Section: Discussionmentioning
confidence: 99%
“…Guinot and colleagues 4 demonstrated a decrease in the duration of NE treatment with the use of Ea dyn . 4 To date, studies that have validated Ea dyn at bedside have used cardiac-output (CO) calibrated pulse contour analysis 3 (PiCCO™ and PULSION™) or oesophageal Doppler. 5 Such monitoring systems need dedicated and specific arterial line and venous access that may limit their use at bedside.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…In the present study, FC always consisted of a 10-minute infusion of 500 ml of lactated Ringer's solution. The indications for norepinephrine were persistent arterial hypotension (SAP less than 100 mmHg and/or MAP less than 65 mmHg) despite FC (13). The non-inclusion criteria were permanent arrhythmia, heart conduction block, the presence of an active pacemaker, poor echogenicity, aortic regurgitation, and right heart failure.…”
Section: Patientsmentioning
confidence: 99%
“…There is wide evidence that V-A (un)coupling is a hemodynamic parameter that is associated with patient outcomes (8,(10)(11)(12)(13). The relevance of V-A (un)coupling as a parameter of hemodynamic optimization in patients with acute circulatory failure could be related to the fact that V-A (un)coupling is a parameter of cardiovascular efficiency whereas the classical hemodynamic parameters are exclusively parameters of cardiovascular efficacy (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The physiology of heart-lung interactions provides an opportunity to study respiratory induced changes in arterial pulse pressure and stroke volume to assess the dynamics of the cardiovascular system. The ratio of pulse pressure to stroke volume variation gives an estimate of dynamic arterial elastance as recently described in a short review and commentary [2] to a prospective, open-label, randomised study using this variable to titrate the infusion of noradrenaline in 118 patients with vasoplegia following cardiac surgery [3]. Using a dynamic arterial elastance > 0.94 to titrate noradrenaline resulted in reduced duration and cumulative dose of noradrenaline infusion, whereas all other variables reflective of tissue perfusion remained unchanged [3].…”
mentioning
confidence: 99%